Enhanced Surface Hydrophilicity of Polysulfone Membrane via Atmospheric Pressure Plasma Jet: A Comparative Evaluation with Low-pressure Plasma - Ruangdit, Soraya; Chittrakarn, Thawat; Sirijarukul, Suksawat; Tirawanichakul, Yutthana; Jaiyu, Arisa; Nisao, Mudtorleb; Kaew-on, Chaiporn (Trends in Sciences, 2025)
Polysulfone, a hydrophobic polymer, requires modifications to its hydrophilicity for applications in water or gas filtration. This study investigates the effectiveness of atmospheric-pressure plasma jet (APPJ) and low-pressure plasma (LPP) techniques in altering the hydrophilicity of polysulfone surfaces. Initially, the membranes were prepared using the dry-wet phase inversion technique. Subsequently, their surfaces were modified using APPJ and LPP treatment. The prepared membranes were exposed to argon plasma gases from APPJ and LPP, both operating power of 60 W and with an exposure time of 4 min. From a physical perspective, APPJ’s ambient operation promoted higher hydroxyl radical (OH) densities (∼1015 cm–3) due to collisions between argon metastables and atmospheric water vapor. In contrast, LPP’s vacuum environment favored ion bombardment mechanisms. Plasma properties were diagnosed using an Optical Emission Spectrometer (OES). Spectroscopic analysis confirmed that the APPJ exhibited a 40% stronger OH emission intensity (309 nm peak) compared to LPP, indicating enhanced surface functionalization. The modified membranes were also evaluated for water contact angle (WCA), surface energy, surface roughness and chemical composition. Surface characterization revealed that the APPJ-treated membranes exhibited superior hydrophilicity, with a lower water contact angle (32.4° ± 1.7°) and higher surface energy (61.3 ± 1.2 mJ/m²) compared to the LPP-treated membranes (36.9° ± 1.0°, 58.6 ± 0.4 mJ/m²). The results from WCA and surface energy indicate that the hydrophilicity of the PSF membrane treated with APPJ was significantly enhanced compared to that of the LPP-treated membrane. Meanwhile, X-ray photoelectron spectroscopy (XPS) and atomic force microscopy (AFM) demonstrated increased oxygen-containing groups and surface roughness post-treatment. Therefore, the APPJ technique emerges as a promising method for enhancing the hydrophilicity of polysulfone membranes due to its operational simplicity, cost-effectiveness, and superior performance. HIGHLIGHTS Polysulfone membranes can be hydrophilized using atmospheric pressure plasma discharge. Comparing to the membrane characteristics of the modified membrane using an atmospheric-pressure plasma jet (APPJ) and a low-pressure plasma (LPP) technique. Atmospheric-pressure plasma jet (APPJ) offers promising results in enhancing the hydrophilicity properties of polysulfone membranes. GRAPHICAL ABSTRACT